2019
DOI: 10.1038/s41598-019-54694-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of cell-free mitochondrial DNA during the early postoperative period in kidney transplant recipients

Abstract: Recent studies indicate that urinary mitochondrial DNA (mtDNA) is predictive of ischemic AKI and is related to delayed graft function (DGF) in renal transplantation. Nevertheless, the clinical implications and prognostic value of urinary mtDNA in kidney transplantation remain undetermined. Here, we aimed to evaluate the associations between cell-free mtDNA and clinical parameters, including pathological findings in allograft biopsy and post-transplant renal function. A total of 85 renal transplant recipients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Urinary levels of cell-free mitochondrial DNA during early post-transplant phase have also been reported to correlate with AR, DGF and short-term renal function [ 76 ].…”
Section: Armentioning
confidence: 99%
“…Urinary levels of cell-free mitochondrial DNA during early post-transplant phase have also been reported to correlate with AR, DGF and short-term renal function [ 76 ].…”
Section: Armentioning
confidence: 99%
“…Recently there has been greater understanding of how mitochondrial metabolism contributes to cell damage in general [15][16][17][18][19], and to poor outcome in transplantation in particular [20][21][22][23][24]. We discuss the mitochondrial and metabolic changes that contribute to tissue damage during transplantation and consider how to target these pathways therapeutically.…”
Section: Organ Preservation During Transplantationmentioning
confidence: 99%
“…In addition, in response to cell death DAMPs such as mitochondrial DNA (mtDNA) are released by damaged mitochondria into the cell, which activate the innate immune response locally [61][62][63]. mtDNA can be released into the circulation and activate immune responses [21,24], as can metabolites such as succinate, which can go on to activate the SUCNR1 receptor and potentially enhance immune responses [64][65][66]. These inflammatory effects can contribute to organ rejection and long-term graft failure.…”
Section: Mitochondrial Metabolic Changes During Organ Implantation Anmentioning
confidence: 99%
See 1 more Smart Citation
“…When the dmtDNA level was >0.133, the probability of DGF in the recipients was 50%. Another study has shown that urinary mtDNA levels are significantly associated with DGF short-term post-transplant renal function, acute rejection of the graft biopsy [ 23 ]. Therefore, dmtDNA could be a new noninvasive predictor of DGF, this finding is of great significance for application in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%